Economic geography determinants of spatial wage disparities in South Africa: Evidence from a firm-level panel - Sanduku Mulumba; Lawrence Edwards; David Oluwatosin Fadiran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
In this paper, we use the new economic geography (NEG) framework to estimate the extent to which spatial wage disparities in the South African manufacturing sector are an outcome of economic forces such as market access. To test the relationship, we use the anonymized tax data on employers and employees made available by the South African Revenue Service and National Treasury in collaboration with UNU-WIDER. We first document the key stylized facts that characterize the spatial distribution of wages across regions in South Africa using exploratory spatial data analysis (ESDA) techniques. We then test for the existence of a wage structure across South African local and metropolitan municipalities, controlling for individual and firm characteristics using a two-stage estimation method. Consistent with the NEG predictions, we find that wages are higher in municipalities that are closer to large markets, as measured by the Harris market potential index. However, much of the wage effect is driven by the income and employment density of the municipality's own market, and not that of surrounding areas. These results point to a combination of large spatial rigidities leading to highly localized effects of market potential, together with wage and productivity effects arising from urban agglomeration economies.
Keywords: R12; R23; O15; 330; new economic geography; spatial wage disparities; firm characteristics; South Africa; exploratory spatial data analysis; two-stage estimation method; market access